Beyond one-size-fits-all Tailoring diversity approaches to the representation of social groups. [article]. - Apfelbaum, E.
When and why do organizational diversity approaches that highlight the importance of social group differences (vs. equality) help stigmatized groups succeed? We theorize that social group members' numerical representation in an organization, compared with the majority group, influences concerns about their distinctiveness, and consequently, whether diversity approaches are effective. We combine laboratory and field methods to evaluate this theory in a professional setting, in which White women are moderately represented and Black individuals are represented in very small numbers. We expect that focusing on differences (vs. equality) will lead to greater performance and persistence among White women, yet less among Black individuals. First, we demonstrate that Black individuals report greater representation-based concerns than White women (Study 1). Next, we observe that tailoring diversity approaches to these concerns yields greater performance and persistence (Studies 2 and 3). We then manipulate social groups' perceived representation and find that highlighting differences (vs. equality) is more effective when groups' representation is moderate, but less effective when groups' representation is very low (Study 4). Finally, we content-code the diversity statements of 151 major U.S. law firms and find that firms that emphasize differences have lower attrition rates among White women, whereas firms that emphasize equality have lower attrition rates among racial minorities (Study 5). -- (from the authors)
Keywords: Stephens, N; Diversity; Equality; Representation; Race; Gender